Diversity of human small intestinal Streptococcus and Veillonella populations. Issue 2 (25th April 2013) - van den Bogert, Bartholomeus; Erkus, Oylum; Boekhorst, Jos; de Goffau, Marcus; Smid, Eddy J.; Zoetendal, Erwin G.; Kleerebezem, Michiel
Abstract: Molecular and cultivation approaches were employed to study the phylogenetic richness and temporal dynamics of Streptococcus and Veillonella populations in the small intestine. Microbial profiling of human small intestinal samples collected from four ileostomy subjects at four time points displayed abundant populations of Streptococcus spp. most affiliated with S. salivarius, S. thermophilus, and S. parasanguinis, as well as Veillonella spp. affiliated with V. atypica, V. parvula, V. dispar, and V. rogosae . Relative abundances varied per subject and time of sampling. Streptococcus and Veillonella isolates were cultured using selective media from ileostoma effluent samples collected at two time points from a single subject. The richness of the Streptococcus and Veillonella isolates was assessed at species and strain level by 16S rRNA gene sequencing and genetic fingerprinting, respectively. A total of 160 Streptococcus and 37 Veillonella isolates were obtained. Genetic fingerprinting differentiated seven Streptococcus lineages from ileostoma effluent, illustrating the strain richness within this ecosystem. The Veillonella isolates were represented by a single phylotype. Our study demonstrated that the small intestinal Streptococcus populations displayed considerable changes over time at the genetic lineage level because only representative strains of a single Streptococcus lineage could be cultivated from ileostoma effluent at both time points.